2013
DOI: 10.1002/eji.201243018
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 limits influenza‐induced inflammation and protects against fatal lung pathology

Abstract: Balancing the generation of immune responses capable of controlling virus replication with those causing immunopathology is critical for the survival of the host and resolution of influenza-induced inflammation. Based on the capacity of interleukin-6 (IL-6) to govern both optimal T-cell responses and inflammatory resolution, we hypothesised that IL-6 plays an important role in maintaining this balance. Comparison of innate and adaptive immune responses in influenza-infected wild-type control and IL-6-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 46 publications
(56 reference statements)
6
126
1
2
Order By: Relevance
“…Lauder et al [26] reported that IL-6 has a critical role in coordinating anti-IAV immunity through its ability to limit inflammation, promote protective adaptive immunity, and prevent fatal immunopathology. It seems that early secretion of IL-6 may create an important line of defense against a fatal course of influenza.…”
Section: In-inoculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauder et al [26] reported that IL-6 has a critical role in coordinating anti-IAV immunity through its ability to limit inflammation, promote protective adaptive immunity, and prevent fatal immunopathology. It seems that early secretion of IL-6 may create an important line of defense against a fatal course of influenza.…”
Section: In-inoculationmentioning
confidence: 99%
“…It seems that early secretion of IL-6 may create an important line of defense against a fatal course of influenza. The results of another study indicate that mice lacking IL-6 are less likely to survive the infection by this means, implying a beneficial effect of IL-6 in controlling the infection [26]. Tumor necrosis factor-a is probably essential for limitation of lung lesions during acute influenza virus infection [27].…”
Section: In-inoculationmentioning
confidence: 99%
“…For example, a remarkably high expression of proinflammatory mediators was detected in lung tissues of 2009 pH1N1 fatal cases, including IL-1ra, IL-6, TNF-α, IL-8, MCP1, MIP 1-β, and IP-10, which correlated with viral load. 35 An essential role for IL-6 in orchestrating antiviral immunity through an ability to limit inflammation and promote protective adaptive immunity against fatal lung injury was recently reported in mice, 36 and GM-CSF-dependent cross-talk between infected alveolar epithelial cells and DCs was crucial for effective viral clearance and recovery from injury in murine viral pneumonia. 37 Regarding the influence of cytokines in the response to influenza vaccine, a recent study reported that vaccine recipients with higher pre-vaccination levels of IL-8 were at higher frequency in sero-responders to trivalent inactivated vaccine compared with non-responders, suggesting that cytokines may influence vaccine outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…It is also important in haematopoiesis and acute phase response. The early secretion of this cytokine may constitute an important line of defence against pathogens (11). IL-10 is a cytokine secreted by various immune cells.…”
Section: Discussionmentioning
confidence: 99%